2015
DOI: 10.1149/2.0161502jes
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Performances of Lithium-Air Cells Assembled with Mixed Electrolytes of Ionic Liquid and Diethylene Glycol Diethyl Ether

Abstract: Ionic liquid-based electrolytes composed of diethylene glycol diethyl ether (DEGDEE) and 1-butyl-1-methyl pyrrolidinium bis(trifluoromethane) sulfonyl imide (BMP-TFSI) were prepared and evaluated for non-aqueous lithium-air cell applications. Adding an appropriate amount of BMP-TFSI to the electrolyte solution improved ionic conductivity, oxidative stability and interfacial stability, and reduced flammability and volatility. When BMP-TFSI was mixed with DEGDEE under optimal condition, the cycle performance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Therefore, the thickness of the nickel foam sheet was regarded as the thickness of the air electrode. The loading of 17 mg/cm 2 was notably high even though the air-electrode in this study was much thicker than the ones in previous reports focusing on the areal capacities, [36][37][38] which indicated the use of a nickel foam sheet was effective for obtaining high-loading air electrodes. Figure 1 shows discharge curves of LAB cells incorporating air electrodes prepared thus.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Therefore, the thickness of the nickel foam sheet was regarded as the thickness of the air electrode. The loading of 17 mg/cm 2 was notably high even though the air-electrode in this study was much thicker than the ones in previous reports focusing on the areal capacities, [36][37][38] which indicated the use of a nickel foam sheet was effective for obtaining high-loading air electrodes. Figure 1 shows discharge curves of LAB cells incorporating air electrodes prepared thus.…”
Section: Resultscontrasting
confidence: 54%
“…Furthermore, it is necessary to evaluate areal discharge/charge capacities to increase practical battery energy density. Recently, some trials [36][37][38] have been reported with a similar view. Y. Lin et al reported holey-graphenebased air electrodes with high loading of up to 10 mg/cm 2 .…”
Section: Introductionmentioning
confidence: 69%
“…A low salt concentration was used to prepare the mixed electrolytes, as higher amounts of salt increased the viscosity, which in turn reduced the ionic conductivity due to an increase in ionic interactions within the solution. 30,33 The contents of ionic liquid in the mixed solutions were 0, 25, 50, 75 and 100% based on volume. The mixed electrolyte systems will be abbreviated as IMI-N, PYR-N, PIP-N, and MOR-N, where N is the volumetric percent of ionic liquid in the mixed electrolyte solutions, and IMI, PYR, PIP and MOR represent type of ionic liquids, i.e., MMEsIm-TFSI, MEEsPyr-TFSI, MEEsPip-TFSI, and MEEsMor-TFSI, respectively.…”
Section: Preparation Of Mixed Electrolytesmentioning
confidence: 99%
“…27,28 Recently, it has been demonstrated that mixed electrolytes composed of organic solvent and ionic liquid could overcome the drawbacks associated with the individual components by combining the useful properties of each constituent. 26,[29][30][31] However, research into ionic liquid-based mixed electrolytes for lithium-oxygen batteries is at an early stage and thus, the studies on mixed electrolytes employing new ionic liquids with different structures deserve to be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 All cells and electrolytes were prepared in an argon-lled glovebox with H 2 O and O 2 contents less than 1 ppm. The organic electrolyte was 1 M lithium bis(triuoromethane) sulfonylimide (LiTFSI) dissolved in tetra(ethylene glycol) dimethyl ether (TEGDME).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%